IDENTIFIKASI DAN PENILAIAN KONDISI PADA JEMBATAN WAI POHON PULE I DAN JEMBATAN WAI POHON PULE II KOTA AMBON - Tetiray, Jondri; Roberth, Herry Henry; Soumokil, Musper David (Jurusan Teknik Sipil, 2024)
Bridges are a means of transportation that have a significant role in the smooth traffic movement. Where the function of a bridge is to connect transportation routes that are separated by rivers, swamps, lakes, straits, canals, highways and other crossings. Because the role of bridges is very important, it is necessary to evaluate the feasibility of the bridge. This research aims to analyze the damage level to the Wai Pohon Pule I and Wai Pohon Pule II Bridges in Ambon City based on the standard Bridge Management System (BMS) assessment. From the research results, there was damage to the Wai Pohon Pule I Bridge and the Wai Pohon Pule II Bridge with the condition values ​​of the bridges being as follows, the Wai Pohon Pule I Bridge with the condition value of the bridge being 3 (Damage that requires immediate action), the Wai Pohon Pule Bridge II with the condition value of the bridge being 3 (Damage that requires immediate action).